Development of the Awash Valley - Anteneh, Addis; Yemanu, Hailu (Zede Journal of Ethiopian Engineers and Architects, 2023)
The Awash River is the only large river which starts and ends within the Empire. It starts from the Highlands of Ginchi, Shoa Governorate General and flows towards the east and north of the country for a total length of about l,200 kms.forming the Awash Valley. Since the valley has considerable potential in water resources, irrigable lands, livestock development and other resources as well and because of its favourable geographical location, its proximity to the market centers and to the sea ports and because of the net work of transportation facilities it enjoys the needs for its immediate development are quite obvious. It was with this in view that in 1962 the Ethiopian Government established the Awash Valley Authority (AV A) as an autonomous public authority to administer and develop the natural resources of the Valley.